Wavepacket insights into the photoprotection mechanism of the UV filter methyl anthranilate - Natércia d. N. Rodrigues (Nature Portfolio, 2018)
Here, the authors explore the ultrafast photodynamics of methyl anthranilate. From the quantum beat behavior, the authors find evidence for ultrafast energy redistribution processes which hinder excited state relaxation, making methyl anthranilate a poor choice for a sunscreen chemical filter.